2016
DOI: 10.1111/hsc.12386
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of self-direction: a systematic review of key areas contributing to service users’ engagement and choice-making in self-directed disability services and supports

Abstract: Self-directed disability support policies aim to encourage greater choice and control for service users in terms of the health and social care they receive. The proliferation of self-directed disability support policies throughout the developed world has resulted in a growing amount of research exploring the outcomes for service users, and their families and carers. Our understanding of the issues faced by people with disabilities, particularly how they make health and social care decisions and the key areas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(322 reference statements)
0
24
1
1
Order By: Relevance
“…Given the wide implementation of self-directed support for people with disability, a growing body of research has sought to provide evidence to better inform the approach. Four literature reviews over the last five years have explored the impact of self-direction for people with disability (Harkes 2014;Sims & Cabrita Gulyurtlu 2014;Crozier et al 2013;Lakhani, McDonald, and Zeeman 2016). Reviews have generally found limited empirical research exploring the impact of approaches on participants and their families (Harkes et al 2014b, Sims & Cabrita Gulyurtlu 2014Crozier et al 2013).…”
Section: Self-directed Policy For People With Disabilities: Research mentioning
confidence: 99%
See 3 more Smart Citations
“…Given the wide implementation of self-directed support for people with disability, a growing body of research has sought to provide evidence to better inform the approach. Four literature reviews over the last five years have explored the impact of self-direction for people with disability (Harkes 2014;Sims & Cabrita Gulyurtlu 2014;Crozier et al 2013;Lakhani, McDonald, and Zeeman 2016). Reviews have generally found limited empirical research exploring the impact of approaches on participants and their families (Harkes et al 2014b, Sims & Cabrita Gulyurtlu 2014Crozier et al 2013).…”
Section: Self-directed Policy For People With Disabilities: Research mentioning
confidence: 99%
“…Reviews have generally found limited empirical research exploring the impact of approaches on participants and their families (Harkes et al 2014b, Sims & Cabrita Gulyurtlu 2014Crozier et al 2013). Findings from the limited research to date suggests that self-directed support has the potential to enable people with disabilities to access health and social support services that they may have not received otherwise (Lakhani, McDonald, and Zeeman 2016), and that this may contribute to their increased quality of life (Harkes, Brown, and Horsburgh 2014;Sims and Cabrita Gulyurtlu, 2014). However, it is also apparent that barriers including inaccessible materials and a lack of professional support in organising resources can potentially prevent the effective engagement of those with disabilities into self-directed models (Sims and Cabrita Gulyurlu, 2014;Lakhani, McDonald, and Zeeman 2016).…”
Section: Self-directed Policy For People With Disabilities: Research mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the impact of cognitive impairment means that some people may require active personal support to make care‐related and other decisions (Lakhani et al. ; Miller et al. ; Office of the Public Advocate, ).…”
Section: Introductionmentioning
confidence: 99%